The structure of immunocompetent decidual cells in recurrent missed abortions - Radović Janošević, Dragana; Popović, Jasmina; Krstić, Miljan; Tubić Pavlović, Aleksandra; Stefanović, Milan; Pop-Trajković, Sonja (Vojnosanitetski pregled, 2017)
Background/Aim. Recurrent or habitual missed abortions (RMA) are defined as three or more consecutive abortions. In the first trimester of pregnancy habitual missed abortions occur in about 1% of population. The aim of this immuno-histochemical study of decidua in RMA of unknown etiology was to identify subpopulations of decidual lymphocytes in recurrent miscarriages and compare the distribution of immunocompetent cells in artificial abortions and RMA. Methods. The study included 30 women with at least 2 consecutive miscarriages in the first trimester of pregnancy. Curettements of the third missed abortion were immunohistochemically analyzed. The control group consisted of 20 women without loaded reproductive anamnesis, with the abortion for social reasons. Criteria for exclusion from the study were diagnosed uterine anomalies, positive screening for thrombophilia and women who suffered from diabetes mellitus and disorders in the function of the thyroid gland. Immunophenotyping was performed by immuno-alkaline phosphatase (APAAP) using monoclonal antibodies: CD 30, CD 45 RO, CD 56 and CD 57, CD 68. Results. The number of missed abortions (1,223) was on the average 9.7% of all deliveriies during the test period. Among them RMA were registered in 52 (4.2%) patients and in 30 (57%) the exact etiology of abortions was not determined. RMA was most common in the 25–34 years of age group. The largest number of RMA showed the ultrasound characteristics of missed abortion in 60% of cases and was in nulliparous patients (76.7%). The number of natural killer (NK) CD56 positive cells did not differ significantly between the types of abortion. In the decidual tissue, a number of NK CD57 positive cells was significantly higher in missed abortions compared to artificial interruptions (p < 0.01). In artificial termination of pregnancy there was an absolute predominance of CD45RO lymphocyte subpopulations, whereas in the RMA group there was slightly greater predominance of CD30 positive cells. The completed analysis showed a significantly higher number of CD68 positive macrophages in a decidual tissue of RMA pregnancy (p < 0.01). Conclusion. The number and phenotypic structure of NK cells are significantly different in normal pregnancy decidua and in RMA. The NK cell dominance is present in the RMA group, in favor of CD56+ and CD 57 of subpopulations with increased CD30 of T lymphocyte subpopulations. Macrophages are more numerous in the decidua of pregnancies ended in abortion, so the cause of RMA of unknown etiology in a number of cases could be disregulation of immunocompetent cells.
Keywords: abortion; habitual; immunohistochemistry; uterus; killer cells; natural; missed; decidua